2018
DOI: 10.1017/wet.2018.49
|View full text |Cite
|
Sign up to set email alerts
|

Managing Wicked Herbicide-Resistance: Lessons from the Field

Abstract: Herbicide resistance is 'wicked' in nature; therefore, results of the many educational efforts to encourage diversification of weed control practices in the United States have been mixed. It is clear that we do not sufficiently understand the totality of the grassroots obstacles, concerns, challenges, and specific solutions needed for varied crop production systems. Weed management issues and solutions vary with such variables as management styles, regions, cropping systems, and available or affordable technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 37 publications
2
36
0
Order By: Relevance
“…However, this is the first time that all traits introduced on the market will already have resistant weed species present somewhere in the US [3]. The development of new herbicide-resistant crops coincides with the grower expectation that new technology will solve herbicide resistance issues [18]. These new trait technologies will require proper stewardship, which includes implementing an Integrated Weed Management (IWM) strategy, using cultural, mechanical, biological, and chemical methods at the appropriate timing [19], and implementing Best Management Practices (BMPs), which are recommendations which may or may not include IWM strategies, to slow the evolution and spread of herbicide-resistant weeds [20].…”
Section: Reliance On Herbicide-resistant Cropsmentioning
confidence: 99%
“…However, this is the first time that all traits introduced on the market will already have resistant weed species present somewhere in the US [3]. The development of new herbicide-resistant crops coincides with the grower expectation that new technology will solve herbicide resistance issues [18]. These new trait technologies will require proper stewardship, which includes implementing an Integrated Weed Management (IWM) strategy, using cultural, mechanical, biological, and chemical methods at the appropriate timing [19], and implementing Best Management Practices (BMPs), which are recommendations which may or may not include IWM strategies, to slow the evolution and spread of herbicide-resistant weeds [20].…”
Section: Reliance On Herbicide-resistant Cropsmentioning
confidence: 99%
“…More high-residue cover crop options besides cereal rye are needed to diversify this practice. In a survey of non-organic grower perceptions on herbicide resistance management, growers have suggested that cover crops can present challenges, and there are few available profitable crops to rotate with corn and soybean [13]. Diversity in crop rotations is recognized as an effective herbicide resistance management tactic because different herbicide sites of action can be used on different crops, which can diversify this management tactic [25].…”
Section: Cover Cropsmentioning
confidence: 99%
“…Grower networks could be a valuable support tool, and would allow for the sharing of specialty equipment, such as interseeders, cover crop roller crimpers, industrial hemp decorticators for fiber, etc. One of the most successful approaches in herbicide resistance management has been a community-based approach, where growers design programs to manage herbicide-resistant weeds in cooperation with academic, government, and industry representatives [13,19]. Growers may feel that herbicide resistance issues will worsen because of the action of their neighbors or others throughout the region, a common pool social dilemma [13,20], however, encouragement should be provided by studies [21,22], which show that following a robust management program, even when other nearby farmers are not, will still result in a higher return on investment compared to not using best management practices [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Farmers appear to share concern over such disincentive effects. The Herbicide Resistance Education Committee (HREC) of the Weed Science Society of America (WSSA) held several listening sessions around the USA to better understand farmer motivations, concerns, and challenges in adopting herbicide resistance management practices . Land tenure (whether a farmer owned or rented land) was among seven primary areas of economic concern that farmers identified.…”
Section: Introductionmentioning
confidence: 99%